Hiddenness Argument and Evolutionary Religion of John L. Schellenberg - Sieczkowski, Tomasz (Hybris, 2020)
In this short essay, I discuss Schellenberg's hiddenness argument and try to answer the question of whether it can be treated as an argument for atheism. Juxtaposing it with the concept of skeptical evolutionary religion developed by the Canadian philosopher, I show that instead of proving the non-existence of God, what this argument does is rather opening the possibility of articulating a new vision of religiosity, appropriate for our species place in evolutionary time.